Estimation of Stature from Second and Fourth Digit Lengths in Young Adults - Mutluay, Şükriye Deniz; Bozkır, Memduha Gülhal (The Bulletin of Legal Medicine, 2019)
Objectives: Estimating stature from long extremity bones, such as femur, humerus, is commonly usedduring forensic examinations. The aim of this study is to estimate stature by anthropometric measurements of right and left-hands second (2D) and fourth digit (4D) lengths. Method:The sample group consisted of 140 young adults, 70 male and 70 females (aged 21-19 years), whose 2D and 4D lengths were measured (using digital vernier caliper) of their left and right hands. One measurement was taken directly from landmarks from the proximal metacarpophalangeal crease to the finger tips. The program SPSS (Version 17.0) was used to make a descriptive analysis, Student’s t-test was usedto analyze the difference in height 2D and 4D between males and females. One-way ANOVA was usedto determine the potential interactions between anthropometric measurements within each other and stature. Pearson Correlation coefficient and related P values were also used. Statistical significance was assigned to p values <0.05. Linear and multiple regressions were also developed. Results:The differences between the right-and the left fingers length values were statistically significant for both sexes (p<0.001). In all, the measurements of males were significantly higher than females. The correlation coefficients between stature and the measurements of second and fourth digit were found to be positive and statistically significant. The highest correlation coefficient between stature and digit length for males regarded the right second digit (r=0.505), and for females, the left second digit (r=0.596). Regression equations were checked for accuracy by comparing the estimated stature and actual stature. Conclusion: Both regression models can...